(untitled) (Bangladesh Journal of Agricultural Research, 2012)
Potato is one of the important food crops in Bangladesh. Its demand is increasing day by day. The Tuber Crop Research Centre (TCRC) of BARI released 40 HYV potato varieties and disseminated them in the farmers fields through different agencies. But most varieties were not adopted well by the farmers due to unknown reasons. Therefore, an attempt was made to assess the level of adoption and profitability of BARI released potato variety at farm level. Data were collected from 150 randomly selected potato farmers from Munshigonj, Bogra and Comilla districts during January-February 2010. The results indicated that 48% potato areas were covered by Diamant variety, 16% by Cardinal, 22% by Granola, and the rest 14% areas were covered by Binella, Asterix, Provento, Felsina, Multa and Hira. The cost of BARI released potato cultivation was Tk 2, 10,629 and Tk 1, 84,135 per hectare on full cost and variable cost basis. The major share of total cost was for seed (42%) followed by fertilizer (21%) and human labour (14%). The average yield of potato was 26 t/ha with gross margin of Tk 1, 51,003 per hectare. The net return of potato cultivation was Tk 1, 24,509 per hectare. The benefit cost ratios were 1.59 and 1.82 on full cost and variable cost basis. Human labour, land preparation, seed, and irrigation had positive and significant effect on potato production. Nonavailability of HYV seed at proper time, lack of technical knowledge, high price of seed and fertilizer, infestation of insect and diseases, and lack of storage facilities were the major problems of potato production. DOI: http://dx.doi.org/10.3329/bjar.v37i1.11189 Bangladesh J. Agril. Res. 37(1): 149-158, March 2012